Inflammatory profile of apical periodontitis associated with liver fibrosis in rats: histological and immunohistochemical analysis - Cantiga-Silva, C. [UNESP]; Estrela, C.; Segura-Egea, J. J.; Azevedo, J. P. [UNESP]; de Oliveira, P. H.C. [UNESP]; Cardoso, C. B.M. [UNESP]; Pinheiro, T. N.; Ervolino, Edilson [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Cintra, Luciano Tavares Angelo [UNESP] (Wiley, 2021)
Aim: To investigate the effects of liver fibrosis (LF) on the pro-inflammatory mediators and periapical bone resorption of apical periodontitis (AP) in rats. Methodology: Forty male Wistar rats were distributed into four groups: C – control, AP – rats with AP, LF – rats with LF, AP + LF – rats with AP and LF. LF was induced by carbon tetrachloride administration for 8 weeks and surgical bile duct ligation for 4 weeks; AP was induced in the teeth of rats by dental pulp exposure to the oral environment for 30 days. Jaws and livers were removed after euthanasia. Haematoxylin and Eosin (H&E) and Picrosirius Red (PSR) staining were used to confirm fibrosis in the livers. The jaws were analysed using H&E staining, immunohistochemical assays of interleukin (IL)-1β, IL-6 and tumour necrosis factor-alpha (TNF-α). Student’s t-test and Mann–Whitney’s U-test were used for statistical analysis (P < 0.05). Results: Inflammatory infiltrate was moderate in the AP group and severe in the AP + LF group (P < 0.05). Periapical bone resorption was significantly larger in the AP + LF group compared with the AP group (P < 0.05). IL-1β, IL-6 and TNF-α levels were significantly higher in AP + LF group when compared to the AP group (P < 0.05). Conclusion: More intense inflammatory infiltrate, greater amounts of pro-inflammatory cytokines and increased periapical bone resorption were observed in the presence of liver fibrosis in rats with exposed pulps.
Keywords: apical periodontitis; cytokines; inflammation; liver fibrosis; oral infection